Shadow Economy in Uzbekistan: National Trends and International Perspectives - Alievich , Abduganiev Jamshid (Universitas Muhammadiyah Sidoarjo, 2025)
There has been a persistent shadow economy in the development of Uzbekistan, existing from an economic transition context along with tax evasion, informal employment, and illicit activities. However, government reforms have not reduced the size of informal sector which stands at about 27.2% of GDP, with the maximum being 52%. Addressing a knowledge gap, this study uses a mixed methods approach of statistical analysis and policy evaluation to analyse the drivers and the implications of the shadow economy. They found that high tax burdens, regulatory barriers, and attitudes among the general public concerning governance promoting informal practices. The results indicate that while recent efforts at curbing corruption and making the economy more open, are assisting in 'shedding' the shadow economy, there are still important yet residual obstacles in formalizing the labor market and achieving equitable economic development. Through these insights it is clear that legislative reforms, digitalization, and international coopeartion is needed to ensure that targeting, long term strategies are used to promote transparency and sustainable growth in Uzbekistan. Highlights: Uzbekistan's shadow economy persists due to high taxes, regulation, and informal practices. Recent reforms aid transparency, but obstacles remain in labor market formalization. Legislative reforms, digitalization, and international cooperation needed for sustainable growth. Key words: shadow economy, Uzbekistan, informal employment, tax evasion, economic reforms, governance, anti-corruption, economic development, regulatory barriers, digitalization.